Constructing female identities : meaning making in an upper middle class youth culture - Proweller, Amira (SUNY series, power, social identity, and education., 1998)
Complementing the several recent studies of how boys take active roles in shaping their personal identities, Proweller (education, DePaul U.) explores one year in the lives of 34 adolescent girls at a historically elite, private, single-sex high school. She finds that the school is less homogeneous and stable along class and race lines than educationists have imagined; and that school officials and parents weave a story of complex and contradictory moments of meaning as the girls mold themselves into raced, classed, and gendered beings. Annotation copyrighted by Book News, Inc., Portland, OR. -- Provided by publisher.